A influ??ncia do self-expandido no comportamento do consumidor em comunidade de marca - Santos, Edna de Souza Machado (2015)
This research, inserted into the marketing area, aims to investigate the influence of self-expanded (ARON et al., 1991) on consumer behavior in the Harley-Davidson brand community, an American brand of motorcycles, worldwide famous, whose owners get together, motivated by the brand for several purposes (SOLOMON, 2011). The problem raised by this research is to understand how is the influence of self-expanded on consumer behavior in the Harley-Davidson brand community. Thus, the rationale for this study lies in the approach taken by the light of the Theory of Planned Behavior (AJZEN, 1985) that consumers are influenced or motivated to participate in collective meetings, taking as a starting point the context in which they live, which is provided by the Harley-Davidson brand and they suffer behavioral changes due to the relationships that establish the self-expanded (ARON et. al., 1991) In addition, the brand has consumers that come together and are formed in a strong community setting out mutual commitments which share the same social identity. (BAGGOZI & DHOLAKIA, 2006; ATKIN, 2007; UNDEWOOD, BOND & BAER, 2001). The relevance of this study points to the fact that brand communities represent the key role study for the area of Marketing in Brazil because they offer conditions for us to investigate and understand, in depth, issues related to consumer behavior, understanding of the influence and the kind of culture that the Brazilian consumer receives in regard to Brand equity (ATKIN, 2007; YOO & DONTHU, 2001; AAKER 1998). The corpus of the research included a survey with 193 participants of brand communities. The methodological approach used was quantitative using the SmartPLS for data analysis. The results show that intergroup relations, with respect to attitudes, wishes and positive emotions are feelings shared and that enhance the desire to participate in the activities of this brand community, which culminates with the expansion of the participant's self Harley-Davidson community for belonging, involvement, social identity and behavior with the brand.